KARAKTERISASI SENSOR MAGNETIK FLUXGATE KUMPARAN SEKUNDER GANDA MENGGUNAKAN ELEMEN SENSOR MULTICORE - Widyaningrum Indrasari; Mitra Djamal; Umiatin Umiatin (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Fluxgate is a magnetic sensor that capable to measure the magnetic field in a very small order. The basic principle of the fluxgate sensor is by comparing the measured magnetic field with the magnetic field reference. In this paper, we describe the characterization of fluxgate magnetic sensor using the double secondary coil design. Configuration of primary coil winding and secondary coil that be used is 4x40 and 2x60. We use vitrovacs 6025Z (1.5 mm width and 0.025 mm thick) as the sensor core. Sensor characterization with varying amounts of the core layer is made to determine the influence of the core layer to the demagnetization factor and the sensor sensitivity. The demagnetization factor is performed by measuring the dimensions of the sensor element and the inductance of the sensor. The inductance of the sensor is measured using a LCR meter GW Instek 829 series at a frequency of 10 kHz. The calculation results show that the increasing amounts of the vitrovac core layer is proportional to the demagnetization factor. To determine the sensor sensitivity, sensor calibration is performed by giving the external field on the calibration coil in a faraday chamber. From the sensor calibration we get the relationship between the external fields with the sensor output voltage. Based on this relationship, we can calculate the sensor sensitivity in working range Â± 4 Î¼T. Sensor sensitivity is inversely proportional to the amounts of vitrovac core layer. Sensor with 2 vitrovac core layers has the highest sensitivity (641 mV / Î¼T), and has the smallest absolute error (0.1 at the point of 3.87 Î¼T). Keywords: fluxgate, external field, vitrovac, sensitivity, demagnetization factor, inductance.